The RNA-binding Protein Fused in Sarcoma (FUS) Functions Downstream of Poly(ADP-ribose) Polymerase (PARP) in Response to DNA Damage - Mastrocola, Adam S. (American Society for Biochemistry and Molecular Biology, 2013)
The list of factors that participate in the DNA damage response to maintain genomic stability has expanded significantly to include a role for proteins involved in RNA processing. Here, we provide evidence that the RNA-binding protein fused in sarcoma/translocated in liposarcoma (FUS) is a novel component of the DNA damage response. We demonstrate that FUS is rapidly recruited to sites of laser-induced DNA double-strand breaks (DSBs) in a manner that requires poly(ADP-ribose) (PAR) polymerase activity, but is independent of ataxia-telangiectasia mutated kinase function. FUS recruitment is mediated by the arginine/glycine-rich domains, which interact directly with PAR. In addition, we identify a role for the prion-like domain in promoting accumulation of FUS at sites of DNA damage. Finally, depletion of FUS diminished DSB repair through both homologous recombination and nonhomologous end-joining, implicating FUS as an upstream participant in both pathways. These results identify FUS as a new factor in the immediate response to DSBs that functions downstream of PAR polymerase to preserve genomic integrity.